2021
DOI: 10.1021/acssuschemeng.0c08829
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Nanostructure of Cholinium Argininate Biomass Solvents

Abstract: Cholinium argininate ([Ch]­[Arg]) and water mixtures are biocompatible solvents which are efficient for the dissolution of various kinds of biomass, but the molecular origins of their efficacy are unresolved. Here, we use neutron diffraction experiments and empirical potential structure refinement fits to reveal the liquid nanostructure of 1:3 [Ch]­[Arg]/water, 1:10 [Ch]­[Arg]/water, and 1:10:0.5 [Ch]­[Arg]/water/guaiacol. Guaiacol addition is studied to probe solvation of a model biomass residue found in lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…Structural and computational studies suggested they can be further polarised by nearby choline groups, to become even stronger H-bond donors. 28 This may be important to intercept the existing lignin–cellulose H-bonds in biomass through a competitive process, making strong H-bond donors a desirable feature to have on the anion sidechain for this application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Structural and computational studies suggested they can be further polarised by nearby choline groups, to become even stronger H-bond donors. 28 This may be important to intercept the existing lignin–cellulose H-bonds in biomass through a competitive process, making strong H-bond donors a desirable feature to have on the anion sidechain for this application.…”
Section: Discussionmentioning
confidence: 99%
“…Between the two comprehensive studies, 23,27 values reported by De Santis et al are significantly higher than those of Liu et al The former is more widely supported by other studies such as ChAsp, Ch 2 Asp and ChArg being room temperature solids. 28,29 Despite the differences in reported values, it is generally agreed that most ChAAILs are highly viscous, making them difficult to handle under room conditions. The presence of additional hydrogen bonding sites on the amino acid side chains, such as Asp − , Arg − , Glu − , His − , etc ., seems to further increase viscosity.…”
Section: Preparation and Physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…17 However, to date, compared with tremendous experimental and theoretical investigations of imidazolium based IL–water mixtures, 18 only a few reports have focused on the interactions and microstructures of [Cho][AA]–water mixtures. And these studies only involve the single AA − anion (such as glycine, 16 lysine 19 and arginine 17 ), the effect of the AA structure on dynamic interactions between [Cho][AA] and water molecules, and on the resulting microstructures are still blank. Based on the fact that the anion structure of the IL plays a predominant role in its interaction ability and application efficiency, 20 the influences of the side chain length and residue functional group of the AA − anion on interactions and microstructures of [Cho][AA]–water mixtures need to be extensively explored to achieve various applications.…”
Section: Introductionmentioning
confidence: 99%